Malamuk – A (West) Frisian loanword in Greenlandic - Bakker, Peter; van der Voort, Hein (Études/Inuit/Studies, 2011)
During the 17th and 18th centuries the Frisians and the Dutch were dominant in the whaling fisheries of the Davis Strait. They also traded with the Inuit and contributed to the Greenlandic pidgin that both parties used as a trade language. Despite intensive interethnic contacts, there are no traces of the Frisian or Dutch languages in modern Greenlandic, with the exception of the word malamuk ‘fulmar.’ In addition, similar forms are also attested in various Germanic languages. Although the exact etymological origin of this word and the precise route by which it ended up in Greenlandic have not been resolved completely, it is beyond doubt that Frisian and Dutch whaling crews were its point of entry.